Living apart together: Niche partitioning among Alboran Sea cetaceans. (December 2018) - Giménez, Joan; Cañadas, Ana; Ramírez, Francisco; Afán, Isabel; García-Tiscar, Susana; Fernández-Maldonado, Carolina; Castillo, Juan José; de Stephanis, Renaud
Highlights: Spatial and trophic niche play an important role in niche partitioning in cetaceans. Cetacean species segregate spatially throughout the bathymetric gradient. Isotopic niche spaces segregate between small and large-sized cetaceans. Investigating niche partitioning in different niche axes is desirable/recommended. Niche partitioning may explain the high abundance of cetaceans in the Alboran Sea. Abstract: Co-occurring species are expected to distribute themselves unevenly throughout ecological niche dimensions to avoid competitive exclusion. However, few studies have previously investigated spatial and trophic factors structuring an entire cetacean community. Here, we combined density surface models (DSMs) with two dimension ( δ 15 N and δ 13 C) isotopic niche spaces in order to identify the mechanistic processes underlying niche partitioning for the most abundant cetacean species inhabiting the Alboran Sea: the long-finned pilot whale ( Globicephala melas ), the Cuvier's beaked whale ( Ziphius cavirostris ), the Risso's dolphin ( Grampus griseus ), the bottlenose dolphin ( Tursiops truncatus ), the striped dolphin ( Stenella coeruleoalba ), and the short-beaked common dolphin ( Delphinus delphis ). DSMs provide a spatially-explicit assessment of species distribution through key spatial and environmental gradients, whereas isotopic niches characterize habitat and resource use. Our isotopic niche approach pointed to habitat and/or trophic segregation between the small (striped and short-beaked common dolphins) and large-sized cetacean species (Risso's and bottlenose dolphins, and long-finned pilot whales). Conversely, DSMs suggested a larger degree of spatial segregation among species by depth, with some overlap for offshore species (long-finned pilot, Cuvier's beaked whales and Risso's dolphins) and also between bottlenose and common dolphins. Thus, both components of the ecological niche apparently played an important role in explaining niche partitioning among species, which, in turn, might explain the high abundance and diversity of cetaceans in the Alboran Sea. Further, when both methodologies were applied in isolation, the structure and functioning of this cetacean community was poorly resolved. The combination of both approaches is therefore desirable when investigating niche partitioning among ecologically similar species within communities.